2011
DOI: 10.1002/bdrb.20290
|View full text |Cite
|
Sign up to set email alerts
|

Developmental toxicity of fungicide carbendazim in female mice

Abstract: This study investigated the developmental toxicity of carbendazim during the organogenesis period in mice. Mated CD-1 mice were administered carbendazim at dose levels 0, 150, 300, and 600 mg/kg/day by gavage. Body weights, weight gains, and feed consumption were significantly reduced in mice administered with 300 and 600 mg/kg/day. Carbendazim exposure increased maternal levels of cholesterol, triglyceride, glucose, protein, and creatinine; and reduced the levels of estradiol and progesterone in the 300- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 40 publications
(34 reference statements)
1
31
0
Order By: Relevance
“…Furthermore, carbendazim exposure strongly affected the development of embryos which is consistent with studies conducted in amphibian (Yoon et al, 2008) and rodent embryos (Farag et al, 2011) where the compound showed to be teratogenic increasing the incidence of malformations such as pericardial edemas, spinal lordosis, elongated heart, narrowed head among others. Similarly to our work, the body length of clawed frog (X. laevis) exposed to carbendazim was also decreased although effects were observed at lower concentrations (≥ 0.38 mg/L) (Yoon et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, carbendazim exposure strongly affected the development of embryos which is consistent with studies conducted in amphibian (Yoon et al, 2008) and rodent embryos (Farag et al, 2011) where the compound showed to be teratogenic increasing the incidence of malformations such as pericardial edemas, spinal lordosis, elongated heart, narrowed head among others. Similarly to our work, the body length of clawed frog (X. laevis) exposed to carbendazim was also decreased although effects were observed at lower concentrations (≥ 0.38 mg/L) (Yoon et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, carbendazim has shown to be very persistent in the water with a half-life of 6 to 25 weeks (Cuppen et al, 2000a). Many studies have reported the adverse effects of carbendazim on mammals, mainly on reproductive organs (Farag et al, 2011;Ireland et al, 1979;Lim and Miller, 1997;Nakai et al, 2002;Urani et al, 1995), but unlike mammals, effects on aquatic organisms are poorly studied. The majority of studies available focus on zooplankton and macroinvertebrate communities in which chronic exposures to carbendazim decreased survival, reproduction and feeding rates (Cuppen et al, 2000b;Daam et al, 2010;Ferreira et al, 2008;Ribeiro et al, 2011;Van den Brink et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It also interferes with male and female fertility (Farag et al, 2011). CA both induces aromatase expression, the enzyme responsible for the conversion of androgens into estrogens, and potently interferes with microtubule polymerization thereby inhibiting mitosis (Yenjerla et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The soil persistence and the plant systemic nature of MBC can in turn, lead to the contamination of water and plant products [5]. This causes serious concerns because MBC is a suspected mutagen, teratogen and carcinogen and is reported to be toxic to mammalian liver, endocrine and reproductive tissues [6], [7]. Residual MBC in soil has also been reported to alter the taxonomic structure of soil bacterial communities and may therefore adversely affect microbial-mediated ecosystem functions [8].…”
Section: Introductionmentioning
confidence: 99%